THE TARGET ACHIEVEMENT EFFORT OF MECHANICAL AVAILABILITY AND PHYSICAL AVAILABILITY OF DOOSAN 500 LCV EXCAVATOR LOADING EQUIPMENT AT PT XYZ - Kemas. Moh. Ade Isnaeni; Isdaryanto Iskandar; Yohana Pita Sibarani (International Journal of Social Science, 2022)
Mechanical earthmoving is all work related to digging, breaking, loosening, loading, hauling, and compacting soil or rock (overburden) using mechanical devices. Based on the results of research in April 2022 it was concluded that mechanical availability and physical availability did not meet the target plan, where the mechanical availability value in April was 74% and the physical availability value in April was 79%. While the value to be achieved at PT XYZ on mechanical availability is 83% and physical availability is 90%. One of the efforts for MA and PA to achieve the target plan is to map actual conditions and then make a work plan.